Street smarts: a remarkable adaptation in a city-wintering raptor - Dinets, Vladimir (Frontiers in Ethology, 2025)
IntroductionUrban birds have to adapt to their complex and challenging environment. In the present study, a particularly remarkable behavioral adaptation by Cooper’s hawk (Accipiter cooperi) was observed.MethodsObservations were conducted visually in urban habitat in New Jersey, where Cooper’s hawks are mostly winter residents.ResultsAn immature Cooper’s hawk was observed hunting birds near a road intersection using queues of cars waiting for green light as cover. The queues grew sufficiently long only when pedestrian crossing regime was activated at the streetlight. The hawk apparently learned to prepare for attack when sound signals indicated the activation of pedestrian crossing regime.DiscussionThe observed behavior required having a mental map of the area and understanding the connection between the sound signals and the change in traffic pattern – a remarkable intellectual feat for a young bird that likely had just moved into the city. Such level of understanding and use of human traffic patterns by a wild animal has never been reported before.